2018
DOI: 10.1007/s11606-018-4435-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of the Effectiveness of Implementation Strategies for Non-communicable Disease Guidelines in Primary Health Care

Abstract: Guideline implementation strategies are heterogeneous. Reducing the complexity of strategies and tailoring to the local conditions and PCPs' needs may improve implementation and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 73 publications
(93 reference statements)
6
32
0
1
Order By: Relevance
“…8,9 Interventions targeting these barriers, such as clinician and patient education or system-level changes like alerts or team-based care, have been shown effective in increasing guideline uptake. 10 However, few studies provide a comprehensive evaluation of how different levels of factors collectively affect guideline uptake. 11 Examining these factors as a whole and how they interact may better inform interventions.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Interventions targeting these barriers, such as clinician and patient education or system-level changes like alerts or team-based care, have been shown effective in increasing guideline uptake. 10 However, few studies provide a comprehensive evaluation of how different levels of factors collectively affect guideline uptake. 11 Examining these factors as a whole and how they interact may better inform interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Factors, such as perceptions of illness by clinicians and unawareness of the published gout treatment recommendations play a vital role in these problems [18,19]. Moreover, the promotion of clinical guidelines through printed material was minimally effective for clinicians [39,40]. The results of our study showed suboptimal management of GF in EDs based on the 2012 TRA-GMG.…”
Section: Discussionmentioning
confidence: 79%
“…Findings from another feasibility study suggested that additional material such as small portable cards with inclusion criteria, telephone numbers and listed referral options are helpful [52]. A meta-analysis of the effectiveness of implementation strategies for non-communicable disease guidelines in primary health care concluded that the simple provision of educational materials without training is ineffective [53]. In line with our ndings, a review on secondary care found that providing information about successful examples can lower implementation barriers and enhance adherence [50].…”
Section: Discussionmentioning
confidence: 79%